Coulomb explosion imaging and covariance analysis of concurrent fragmentation mechanisms - Walmsley, TR (2024)
This thesis uses Coulomb explosion imaging and covariance analysis to characterise concurrent fragmentation processes generating identical sets of products via different reaction pathways, highlighting the potential of extending these methods to study the photochemistry of larger, more chemically relevant species than those that have previously been studied.